2017
DOI: 10.1128/jvi.02396-16
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus NS1 Antagonizes Interferon Beta Production by Targeting RIG-I and MDA5

Abstract: West Nile virus (WNV) is a mosquito-borne flavivirus that causes epidemics of encephalitis and viscerotropic disease worldwide. This virus has spread rapidly and has posed a significant public health threat since the outbreak in New York City in 1999. The interferon (IFN)-mediated antiviral response represents an important component of virus-host interactions and plays an essential role in regulating viral replication. Previous studies have suggested that multifunctional nonstructural proteins encoded by flavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 61 publications
(83 reference statements)
1
71
0
Order By: Relevance
“…During virus invasion, multiple signaling pathways can be activated to facilitate the high expression of type I IFN and downstream antiviral genes, mainly including RLRs and TLRs (29,30). Previously, it has been extensively shown that flaviviruses, such as dengue virus (DENV), hepatitis C virus, and West Nile virus, can target the RLR pathway, thus blocking the key processes of type I IFN signal transduction and antagonizing the innate immunity with different molecular mechanisms (22,23,31). To explore the potential correlation between NS3/NS2B3-mediated IFNb antagonism and RLR signaling pathway, we constructed Flag-tagged RIG-I-2CARD, MAVS, MITA, TBK1, IRF3-5D expression plasmids and then cotransfected them with HA-tagged NS3 or NS2B3 into HEK293T cells.…”
Section: Zikv Ns3 and Ns2b3 Attenuate Ifn-b Expressionmentioning
confidence: 99%
“…During virus invasion, multiple signaling pathways can be activated to facilitate the high expression of type I IFN and downstream antiviral genes, mainly including RLRs and TLRs (29,30). Previously, it has been extensively shown that flaviviruses, such as dengue virus (DENV), hepatitis C virus, and West Nile virus, can target the RLR pathway, thus blocking the key processes of type I IFN signal transduction and antagonizing the innate immunity with different molecular mechanisms (22,23,31). To explore the potential correlation between NS3/NS2B3-mediated IFNb antagonism and RLR signaling pathway, we constructed Flag-tagged RIG-I-2CARD, MAVS, MITA, TBK1, IRF3-5D expression plasmids and then cotransfected them with HA-tagged NS3 or NS2B3 into HEK293T cells.…”
Section: Zikv Ns3 and Ns2b3 Attenuate Ifn-b Expressionmentioning
confidence: 99%
“…Many viruses have developed different mechanisms to escape the antiviral response, including counteracting the activity of ISG15 (Guerra, Cáceres, Knobeloch, Horak, & Esteban, ; Yuan & Krug, ). Several studies have addressed NNV persistent infections in many fish, indicating NNV has developed some mechanisms to antagonize host innate antiviral responses (Lu et al, ; Zhang et al, ). We speculated that RGNNV might counteract the antiviral activity of ISG15 to escape the host antiviral response in LJB cells.…”
Section: Discussionmentioning
confidence: 99%
“…In Figs. 3 and 4, the HEK293 T cells were seeded in 24-well plates and transfected with the Flag-nsp16, Myc-nsp10, IFN-β-luc reporter, the LacZ and poly I:C or Flag-RIG-I(N) or Flag-MDA5(N) (Zhang et al, 2017) for 24 h and then the cells were lysed for luciferase assays and western blotting.…”
Section: Luciferase Assaymentioning
confidence: 99%